Implementasi Aplikasi QOMARUN sebagai Sistem Informasi Pelaporan dan Pencegahan Kekerasan Berbasis Web di Pondok Pesantren Miftahul Ulum Gondok - Satria Yudha Nugraha; Miftah Farid Adiwisastra; Yani Sri Mulyani (Riau Jurnal Teknik Informatika, 2026)
This study aims to implement QOMARUN, a web-based information system for reporting and preventing violence in Islamic boarding schools (pondok pesantren). The study addresses the lack of a secure and transparent reporting mechanism, which causes many violence cases to remain unreported. The system was developed using the Prototyping method and implemented with Laravel framework based on the Model-View-Controller (MVC) architecture, supported by Livewire and Tailwind CSS. System evaluation was conducted through black-box testing and a user questionnaire involving one respondent with 15 Likert-scale statements. The results showed that all core system functions operated successfully, while the questionnaire achieved an average score of 3.67 out of 5, indicating positive user acceptance. The QOMARUN application provides a secure, structured, and transparent reporting mechanism and has the potential to improve violence reporting and case management in Islamic boarding schools.